2011
DOI: 10.1107/s1600536811002674
|View full text |Cite
|
Sign up to set email alerts
|

Cinnarizinium dipicrate

Abstract: In the cinnarizinium dication of the title compound {systematic name: 1-diphenyl­methyl-4-[(2E)-3-phenyl­prop-2-en-1-yl]piperazine-1,4-diium bis­(2,4,6-trinitro­phenolate)}, C26H30N2 2+·2C6H2N3O7 −, the piperazine group is protonated at both N atoms and adopts a slightly distorted chair conformation. Strong N—H⋯Ohy­droxy cation–anion hydrogen bonds link the dication and two anions. In the cation, the (2E)-3-phenyl­prop-2-en-1-yl fragment is disordered over two positions in a ratio of 0.586 (4): 0.414 (4). Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…For related structures, see: Bertolasi et al (1980);Smith et al (2001); Jasinski et al (2011). For puckering analysis, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For related structures, see: Bertolasi et al (1980);Smith et al (2001); Jasinski et al (2011). For puckering analysis, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…A clinical evaluation of cinnarizine in various allergic disorders is published (Barrett & Zolov, 1960). The crystal structures of some related compounds such as cyclizine hydrochloride (Bertolasi et al, 1980), guanidinium 3,5-dinitrosalicylate (Smith et al, 2001) and cinnarizine dipicrate (Jasinski et al, 2011) have been reported.…”
Section: Commentmentioning
confidence: 99%
“…For background to the anti-histamine cinnarizine, see: Towse (1980); Barrett & Zolov (1960). For related structures, see: Mouillé et al (1975); Bertolasi et al (1980); Jasinski et al (2011). For additional conformational analysis, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…For the biological activity of piperazines, see: Brockunier et al (2004); Bogatcheva et al (2006). For related structures, see: Anilkumar et al (2005); Betz et al (2011); Fun et al (2011); Jasinski et al (2010Jasinski et al ( , 2011; Dutkiewicz et al (2011). For graphset analysis of hydrogen bonds, see: Etter et al (1990); Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…They are found in biologically active compounds across a number of different therapeutic areas such as antifungal, antibacterial, antimalarial, antipsychotic, antidepressant and antitumour activity against colon, prostate, breast, lung and leukemia tumors (Brockunier et al, 2004;Bogatcheva et al, 2006). The crystal structures of some related compounds, viz., 2-(2phenylethyl)benzoic acid (Anilkumar et al, 2005), levocetirizinium dipicrate (Jasinski et al, 2010), cinnarizinium dipicrate (Jasinski et al, 2011), 1-methylpiperazine-1,4-diium dipicrate (Dutkiewicz et al, 2011) and 4-(4-chlorophenyl)-4-hydroxypipe ridinium 2-(2-phenylethyl)benzoate (Fun et al, 2011) have been reported. Recently, we have reported the crystal structure of 4-[bis(4-fluorophenyl) methyl]piperazin-1-ium picrate (Betz et al, 2011).…”
Section: S1 Commentmentioning
confidence: 99%